1999
DOI: 10.1016/s0092-8674(00)80798-9
|View full text |Cite
|
Sign up to set email alerts
|

Pak Functions Downstream of Dock to Regulate Photoreceptor Axon Guidance in Drosophila

Abstract: The SH2/SH3 adaptor protein Dock has been proposed to transduce signals from guidance receptors to the actin cytoskeleton in Drosophila photoreceptor (R cell) growth cones. Here, we demonstrate that Drosophila p21-activated kinase (Pak) is required in a Dock pathway regulating R cell axon guidance and targeting. Dock and Pak colocalize to R cell axons and growth cones, physically interact, and their loss-of-function phenotypes are indistinguishable. Normal patterns of R cell connectivity require Pak's kinase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
209
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(227 citation statements)
references
References 36 publications
17
209
0
1
Order By: Relevance
“…Among other structural features, the Drosophila Trio contains a motif of DH-PH ± DH-PH tandem domains, the characteristic feature of GEFs speci®c for the Rho family GTPases. It was shown that Trio localizes at the growth cone membrane and that the trio mutant disrupted the photoreceptor axon projection patterns (Newsome et al, 2000), defects similar to those seen in both Pak and dock mutants (Garrity et al, 1996;Hing et al, 1999). This function of Trio in axon guidance depended upon its GEF activity, since mutation in one of two GEF domains of Trio completely abolished the Trio function.…”
Section: Nck Links Cell Surface Receptors To the Actin Cytoskeletonmentioning
confidence: 90%
See 3 more Smart Citations
“…Among other structural features, the Drosophila Trio contains a motif of DH-PH ± DH-PH tandem domains, the characteristic feature of GEFs speci®c for the Rho family GTPases. It was shown that Trio localizes at the growth cone membrane and that the trio mutant disrupted the photoreceptor axon projection patterns (Newsome et al, 2000), defects similar to those seen in both Pak and dock mutants (Garrity et al, 1996;Hing et al, 1999). This function of Trio in axon guidance depended upon its GEF activity, since mutation in one of two GEF domains of Trio completely abolished the Trio function.…”
Section: Nck Links Cell Surface Receptors To the Actin Cytoskeletonmentioning
confidence: 90%
“…These studies suggested that these Ste-20-related protein kinases are important downstream targets for Nck. In collaboration with Louis Lim's group, Zipursky and colleagues reported that, Pak, one of the three Drosophila Pakrelated molecules (Pak, Mbt and Dpak2), is required for the Dock pathway regulating R cell axon guidance and targeting (Hing et al, 1999). Mbt and Dpak2 did not bind Dock and had no e ect on the R cell axon guidance.…”
Section: Nck Links Cell Surface Receptors To the Actin Cytoskeletonmentioning
confidence: 99%
See 2 more Smart Citations
“…L'un des effecteurs de Cdc42, N-WASP (Wiskott-Aldrich syndrome protein), essentiel pour la formation des filopodes induite par [16]. Dans les photorécep-teurs de drosophile, des mutations entraînant une perte de fonction de PAK1 provoquent des défauts dans le guidage axonal [17,18]. PAK possède plusieurs cibles, dont la LIM kinase (Lim-11, Isl-1, Mec-3 domains kinase) et la MLCK (myosin light chain kinase).…”
Section: Protéines Rho Et Effecteurs: Effet Sur Le Cytosquelette D'acunclassified